2018
DOI: 10.2993/0278-0771-38.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Urban Allotment Gardens in Poland: Implications for Botanical and Landscape Diversity

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…The same studies also recorded low synanthropization levels and very few invasive species. They also confirmed that generally urban gardeners were attached to traditional foods and ornamental plants [32,41].…”
Section: Research Questionsmentioning
confidence: 55%
See 2 more Smart Citations
“…The same studies also recorded low synanthropization levels and very few invasive species. They also confirmed that generally urban gardeners were attached to traditional foods and ornamental plants [32,41].…”
Section: Research Questionsmentioning
confidence: 55%
“…Besides, numerous studies conducted in relation to different Polish cities showed that AGs exhibited high plant species richness and diversity. The study conducted in 2009 among 46 urban allotment gardeners in three Polish cities documented 257 botanical taxa [32] and 358 species of flora recorded in 11 representative allotment garden estates (total area 150 ha) in the city of Poznań [41]. The same studies also recorded low synanthropization levels and very few invasive species.…”
Section: Research Questionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is possible that allotment gardens can play a role in this important field [9]. The abundance of plant species and the diversified manner of allotment garden utilization are worth emphasizing [15]. The benefits of providing urban vegetation [16], the therapeutic and nutritional value of gardens [17,18], the psychological benefits [19,20], the social well-being of gardeners [21] and the benefits of local food production [22] may be some examples of this.…”
Section: Introductionmentioning
confidence: 99%
“…Ninety percent of allotment gardens in Poland are located in urban areas [30]. However, in the five largest (by total area) Polish cities (Warszawa, Kraków, Szczecin, Łódź, and Wrocław), the share of gardens is less than 5% (Table 1.)…”
Section: Uags In Polandmentioning
confidence: 99%